Plant Protection Measures use Behaviour of Vegetable Growers in Punjab State - Gill, Jagjeet Singh; Sharma, Anil; Sharma, Surabhi (Indian Journal of Extension Education, 2020)
Vegetables are short duration crops and they provide handsome income to meet the day to day need. Vegetable farming is important for the small farmers as 80 per cent of farmers in our country are small and marginal farmers and it addresses the nutrition security issue. Major share of the input cost in vegetable production is spent on pesticides. The judicious use of these pesticides can increase the farmer’s income as most of the respondents face the problems of insects/pests, diseases and weeds. The study conducted on 200 vegetable growers in Jalandhar and Moga districts of Punjab state showed that most of the respondents were potato growers and more than half of the total respondents faced problem of insect/pest in potatoes. Respondents had very less awareness about spray uniform and antidotes. All the respondents washed hands after the spray of insecticide/pesticide.
Keywords: Awareness; Disease control; Insect/pest; Pesticide; Vegetables